Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae) - Javidkar, Mohammad; King, Rachael A.; Cooper, Steven J. B.; Humphreys, William F.; Austin, Andrew D. (Zootaxa, 2017)
The oniscidean fauna of Australia is generally poorly known but recent sampling has revealed a new family, Paraplatyarthridae, found in both terrestrial and groundwater calcretes of central Western Australia. The family was initially described based on a new genus and species, Paraplatyarthrus subterraneus Javidkar and King, 2015. Here we describe an additional five Paraplatyarthrus species from the Yilgarn region of Western Australia, based on both morphological and molecular evidence (COI divergences). Four species are subterranean: P. crebesconiscus Javidkar and King sp. nov., P. cunyuensis Javidkar and King sp. nov., P. occidentoniscus Javidkar and King sp. nov., and P. pallidus Javidkar and King sp. nov., and one is a surface species, P. nahidae Javidkar and King sp. nov. A key to their identification is provided along with information on their distribution. In addition, type material of the two described Australian species of Platyarthridae, Trichorhina australiensis Wahrberg, 1922 from Western Australia and T. tropicalis Lewis, 1998 from Queensland, are examined. Morphological reassessment of type material shows T. australiensis belongs to Paraplatyarthrus (comb. nov.) and that T. tropicalis is correctly placed in Trichorhina, confirming that the genus and family Platyarthridae occur in Australia.